Antagonistic interaction between heterotrophic bacteria and cyanobacteria Biocontrol of algal blooms - Omneya Ahmed Osman; Stefan Bertilsson (Uppsala University, 2015)
Metatranscriptomic data of antagonistic interaction between cyanobacteria and heterotrophic bacteria after 24 h incubation time
Keywords: Metagenomic sequence data; Medical and Health Sciences; Medicin och hälsovetenskap